Evaluation of the Biogenic Amines Formation and Degradation Abilities of Lactobacillus curvatus From Chinese Bacon - Li, Lu; Wen, Xiaoxue; Wen, Zhiyou; Chen, Shouwen; Wang, Ling; Wei, Xuetuan (Frontiers in Microbiology, 2018)
Control of biogenic amines (BAs) is critical to guarantee the safety of fermented meat products. The aim of this study is to evaluate the BAs formation and degradation abilities of lactic acid bacteria from Chinese bacon to obtain the beneficial candidate for BAs control. Seven lactic acid bacteria were selected from the typical Chinese bacon products, identified as Lacbacillus curvatus by 16S rDNA analysis. Then, genes analysis and high performance liquid chromatography (HPLC) analysis were performed to evaluate the BAs formation and degradation abilities of as-selected strains. All L. curvatus strains were confirmed to harbor the genes encoding the tyrosine decarboxylase and ornithine decarboxylase, and they could produce tyramine, β-phenethylamine, putrescine and cadaverine. In comparison, the lowest concentration of total BAs was obtained in L. curvatus G-1. Meanwhile, all L. curvatus strains were positive in amines oxidase gene analysis, and they could also degrade six common BAs, especially the L. curvatus G-1 with the highest degradation percentage (above 40%) for each BA. Furthermore, fermented meat model analysis verified that the L. curvatus G-1 could significantly reduce BAs. In conclusion, L. curvatus G-1 shows a low BAs-producing ability, as well as a high BAs-degrading ability, and this study provides a promising candidate for potential BAs control in fermented meat products.